KONTEKS MAKKIYAH DAN MADANIYAH SISTEM KALENDER UMAT ISLAM: Sebuah Tinjauan Semantik atas Term-term dalam Ayat dan Hadis tentang Hisab dan Ru’yah - Musonnif, Ahmad (Ahkam: Jurnal Hukum Islam, 2017)
Term hiisab, ummii, and other words associated with determining the beginning of the hijriyah months sometimes has been interpreted as less precise on its context. Hermeneutical approach with semantic methods is needed to help finding the meaning of the words and its context on the time when it was used. Hisaab (calculation), in the context of Mecca, means reckoning the manzilah of moon which was related to seasons and the system of nasii’ (intercalation). In the context of Medina, hiisaab (calculation) refers to methods of calendar of ahl al-kitaab (Jews or Christians). While the meaning of ummii is often misunderstood as ‘cannot write and count’. In the context of its semantic meaning ummii means non-Jews or non-ahl al-kitaab.Keywords: Kalender, Makkiyah, Madaniyah, Semantik